Characterization and evaluation of antimicrobial properties of electrospun chitosan/polyethylene oxide based nanofibrous scaffolds (with/without nanosilver). (January 2015) - Erdem, Ramazan; Akalın, Mehmet
Various ratios (30/70%, 70/30%, 50/50% with and without nanosilver) of chitosan (CS; 60–120.000 g/mol) and polyethylene oxide (PEO; 600.000 g/mol) blended nanofibers in the nanofibrous scaffolds were obtained by using electrospinning at ambient atmosphere. Homogenous CS solutions were prepared in 90% aqeous acetic acid. PEO was dissolved in deionized water. Nanosilver dispersion was prepared and added to the 50/50% blend of CS/PEO solution. Properties of all blended solutions were determined by measuring viscosity and conductivity. Differential scanning calorimeter, Fourier transform infrared spectroscopy, scanning electron microscopy analysis and tensile tests were conducted to investigate the characteristics of the final nanofibrous composite structures. Beadless and uniform nanofibers were obtained and the average diameter of the fibers ranged from 63 ± 23 nm to 108 ± 51 nm. The antimicrobial effectiveness of the nanofibrous scaffolds was investigated against Escherichia coli and Candida albicans, and satisfactory results were obtained.